Adsorption of Water on Vacancy Defective h-BN Bilayer at B and N Sites: First-principles calculation - Nepal, Madhav; Paudel, Ganesh; Aryal, Santosh; Devkota, Arun; Neupane, Hari Krishna (BIBECHANA, 2024)
<>Two dimensional (2D) materials are used to manufacture the various gadgets. Their properties are therefore appealing. In the present work, we have studied the structural, electronic, and magnetic properties of 2D bilayer hexagonal-Boron Nitride (h-BN), single B vacancy defect on h-BN (B-hBN), single N vacancy defect on h-BN (N-hBN), water adsorption; on B-hBN (w-B-hBN) and on N-hBN (w-N-hBN), materials by spin-polarized density functional theory (DFT) methods employing Quantum ESPRESSO (QE) computational tools. The structural stability of the h-BN, B-hBN, N-hBN, w-B-hBN, & w-N-hBN materials has been investigated by determining their minimum ground state energy and binding energy, and found that they are stable materials. The pristine h-BN bilayer supercell structure is also found to be more compact than other defective configurations. By analyzing the band structures and density of states (DoS) plots of these materials, we have examined their electronic properties, and found that pristine h-BN has a broad bandgap, whereas B-hBN, N-hBN, w-B-hBN, & w-N-hBN exhibit semiconducting nature. The DoS and partial density of states (PDoS) computations of the considered materials are used to study their magnetic properties. It is found that pristine h-BN is a non-magnetic, and B-hBN, N-hBN, w-B-hBN & w-N-BN are magnetic materials. Therefore, vacancy defects on pristine h-BN, and water adsorption on vacancy defected h-BN materials cause it to change from non-magnetic to magnetic. They could find use in the domain of device applications.